John Cumiskey papers - Cumiskey, John, approximately 1828-1863.
AlsS written by Cumiskey to his wife, Rose Cumiskey, during his Civil War service with Company I, 17th Connecticut Infantry Regiment. Cumiskey describes conditions and activities of his company in Baltimore, Md., Washington, D.C., and Virginia prior to his death in 1862. Includes correspondence relating to Cumiskey's death, burial in 1863, and eligibility for pension; typewritten transcripts of several letters; an 1854 letter informing Cumiskey of his mother's death; a tintype of Cumiskey in uniform, circa Sept. 1862; and a newspaper clipping (circa 1925).
Union Army soldier and farmer of Greenwich, Conn.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Cumiskey, Rose -- Correspondence; United States. -- Army -- Military life; United States. -- Army. -- Connecticut Infantry Regiment, 17th (1862-1865). -- Company I; Baltimore (Md.) -- History -- Civil War, 1861-1865.; Connecticut -- History -- Civil War, 1861-1865.; Maryland -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; Washington (D.C.) -- History -- Civil War, 1861-1865.; Farmers; Soldiers